Fuzzy logic model-based punch force prediction for deep drawing of high strength steel. (2022) - Maanav Charan, K.S.; Aswin, Alenkar K.; Elango, M.; Sivarajan, S.
Abstract: The process of sheet metal forming is referred to as Deep Drawing. It is applied to make hollow–curved metal surfaces using a die and punch which creates the hollow burrow. This process is widely used in various industries to form sheet metals into automatic parts of certain requirements. The punch force applied in the die depends upon various parameters. The punch force is also responsible for the effective outcome of the deep drawing of the metal sheet. Thus, a set of process parameters that majorly affects the punch force is decided and those experiments were done to obtain the punch force at different values for different input parameters. Producing punch force requires huge energy expenditure. Hence, for the process to be both economical and efficient – lower punch forces are preferred. But when multiple parameters are considered, it becomes difficult to obtain the lowest punch force value. Hence, with the L27 orthogonal array, the number of combinations of the experiments that need to be done is reduced phenomenally. These experimental data were used to create a fuzzy logic model using MATLAB software. Therefore, a Fuzzy Logic Model was generated with the considered parameters being the input and the punch force being the output. This model will be used for punch force prediction as well as finding the optimized input parameters to achieve the lowest punch force.